2019
DOI: 10.21153/jtlge2019vol10no1art781
|View full text |Cite
|
Sign up to set email alerts
|

A pre-post evaluation of an online career planning module on university students’ career adaptability

Abstract: Indecisiveness and negative thinking regarding career pathways can hinder university students’ career planning, motivation, and mental health. Students intending to enter the workforce after graduation therefore need to develop skills related to career adaptability (i.e. career planning, decision-making, problem solving/confidence and exploration), particularly since career planning and construction is linked to gaining employment. This study aimed to test the effectiveness of an online career planning module … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 16 publications
(29 reference statements)
2
19
0
1
Order By: Relevance
“…Online career interventions can be highly efficient and are likely to be used increasingly in the future (Dozier et al, 2015). The effectiveness of online career interventions is widely acknowledged (Nota et al, 2016;Teychenne et al, 2019; has not yet been confirmed in the Chinese context, a fact supporting the need for the current study.…”
Section: Literature Review Career Interventionmentioning
confidence: 78%
“…Online career interventions can be highly efficient and are likely to be used increasingly in the future (Dozier et al, 2015). The effectiveness of online career interventions is widely acknowledged (Nota et al, 2016;Teychenne et al, 2019; has not yet been confirmed in the Chinese context, a fact supporting the need for the current study.…”
Section: Literature Review Career Interventionmentioning
confidence: 78%
“…Category (a) has been assessed by the Career Decision-Making Difficulties Questionnaire (Di Fabio & Maree, 2013; Lam & Santos, 2018; Rowell et al, 2014). Category (b) has been assessed by the Career Decision-Making Self-efficacy Scale–Short Form (Behrens & Nauta, 2014; Maples & Luzzo, 2005; McKay et al, 2005; Talib et al, 2015; Tirpak & Schlosser, 2013), the Career Decision Self-Efficacy Scale–Short Form (Di Fabio & Maree, 2013; Lam & Santos, 2018; Teychenne et al, 2019), and the Career Confidence Scale (Peng, 2000). Category (c) has been assessed by the Career Decision Scale (Barclay & Stoltz, 2016a; Lam & Santos, 2018; Peng, 2001; Peng & Herr, 2000) and the Career Factory Inventory (Behrens & Nauta, 2014; Teychenne et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…To answer the research question, we developed a web-based application to support student career counseling [8]. Career counseling aims to make students understand their potential well, know the various jobs and departments at the University [36], and improve confidence regarding job ideas/making career choices [37]. Instead, secondary school students are in their teens, transitioning from childhood to adulthood.…”
Section: Usabilitymentioning
confidence: 99%